2016
DOI: 10.3168/jds.2015-10694
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial subclinical mastitis and its effect on milk yield in low-input dairy goat herds

Abstract: The objectives of this study were (1) to record the major pathogens associated with subclinical mastitis (SCM), (2) to calculate their incidence during the milking period, and (3) to estimate the effect of SCM on daily milk yield (DMY) for goats reared under low-input management schemes. Dairy goats (n=590) of Skopelos and indigenous Greek breeds from 4 herds were randomly selected for the study. The study included monthly monitoring, milk yield recording, and bacteriological analyses of milk of individual goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 33 publications
7
63
0
6
Order By: Relevance
“…Already Bergonier et al (2003b) reported a CNS prevalence in subclinical mastitis ranging from 25 to 93%. Similar results (42.9%) were recently observed also in Portugal in milk samples from clinically affected sheep udders ( Queiroga, 2017 ), in Iran in subclinical ovine mastitis ( Narenji Sani, Mahdavi & Moezifar, 2015 ), in Greece in dairy goats ( Gelasakis et al, 2016 ) and in Italy in both species ( Dore et al, 2016 ). The identification of Staphylococcus xylosus in sheep and Staphylococcus caprae in goats is also in agreement with the literature ( Bergonier et al, 2003b ; Contreras et al, 2007 ; Ergün et al, 2009 ), while Staphylococcus equorum was isolated only by Hariharan et al (2004) in sheep and by Contreras et al (2003) in goats.…”
Section: Discussionsupporting
confidence: 88%
“…Already Bergonier et al (2003b) reported a CNS prevalence in subclinical mastitis ranging from 25 to 93%. Similar results (42.9%) were recently observed also in Portugal in milk samples from clinically affected sheep udders ( Queiroga, 2017 ), in Iran in subclinical ovine mastitis ( Narenji Sani, Mahdavi & Moezifar, 2015 ), in Greece in dairy goats ( Gelasakis et al, 2016 ) and in Italy in both species ( Dore et al, 2016 ). The identification of Staphylococcus xylosus in sheep and Staphylococcus caprae in goats is also in agreement with the literature ( Bergonier et al, 2003b ; Contreras et al, 2007 ; Ergün et al, 2009 ), while Staphylococcus equorum was isolated only by Hariharan et al (2004) in sheep and by Contreras et al (2003) in goats.…”
Section: Discussionsupporting
confidence: 88%
“…They report that culture-negative mastitis which contained >1×10 6 SCC/ml resulted in 43.9% (n = 466) mastitic milk, showing that high SCC does not indicate mastitis infection. In the current study, only Staphylococcus aureus (38.6%) and Escherichia coli (22.9%) were isolated, mainly due to poor milking hygiene (Murphy et al, 2007;Persson and Olofsson, 2011;Gelasakis et al, 2016) and these findings corroborate with the current study.…”
Section: Isolated Pathogenssupporting
confidence: 91%
“…In Kenya, Ndegwa et al, (2000) reported a subclinical mastitis prevalence using three measures, which was 9.8% by CMT, 9.7% by direct leukocyte counts and 28.7% by bacterial isolation. However, White and Hinckely (1999) and Gelasakis et al, (2016) have reported a prevalence rate of 31.7% to 36.4% (n = 1061). Bacterial organisms were isolated in 127 cases (22.5%) of CMT-negative samples.…”
Section: Somatic Cell Countsmentioning
confidence: 95%
See 1 more Smart Citation
“…(Kumar et al, 2016;Rashid et al, 2017). Earlier, the highest prevalence of Coagulase Negative Staphylococci (CNS) was reported by Gelasakis et al (2016), Nickerson et al (2015) and Silanikove et al (2014). Other than single infection (85%), mixed infections (15%) were also found in this study which was supported by the observation of Sarker and Samad (2011).…”
Section: Discussionmentioning
confidence: 99%